2023
DOI: 10.1021/acs.orglett.3c03323
|View full text |Cite
|
Sign up to set email alerts
|

Organoboron/Palladium Cocatalytic Allylation of NH-Sulfoximines Using Allylic Alcohols

Matthew T. Zambri,
Celine Ho,
Mark S. Taylor

Abstract: Synergistic organoboron/palladium cocatalysis enables dehydrative couplings of NH-sulfoximines with allylic alcohols, furnishing the corresponding N-allylated products. The reactions proceed in the absence of a Brønsted base and are tolerant of diverse sulfoximine partners, including functionalized variants. Experimental and computational studies suggest that the sulfoximine reagent is activated by complexation to the boronic acid cocatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In this regard, few articles have discussed the preparation of N -alkyl sulfoximines. 14–16 However, methods for installation of substituents at the α-position of the N -alkyl group are highly limited. Bolm et al developed metal catalyzed cross-dehydrogenative coupling (CDC) and photocatalytic approaches in 2014 17 (Scheme 1a) and 2018 18 (Scheme 1b), respectively, to synthesize N -(α-substituted) alkyl sulfoximines.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, few articles have discussed the preparation of N -alkyl sulfoximines. 14–16 However, methods for installation of substituents at the α-position of the N -alkyl group are highly limited. Bolm et al developed metal catalyzed cross-dehydrogenative coupling (CDC) and photocatalytic approaches in 2014 17 (Scheme 1a) and 2018 18 (Scheme 1b), respectively, to synthesize N -(α-substituted) alkyl sulfoximines.…”
Section: Introductionmentioning
confidence: 99%
“…By employing allylic alcohols as the electrophiles in the presence of a palladium bis­(phosphine) cocatalyst, regioselective dehydrative N-allylations of various azoles were achieved (Scheme ). Control experiments showed that the organoboron catalyst has a significant effect on both reaction rate and N-allylation regioselectivity, suggesting that it plays a role both in activating the allylic alcohol electrophile, in cooperation with the Xantphos­(Pd) complex, and the azole nucleophile. , The allylation method has been extended to other NH-pronucleophiles, including pyridones and sulfoximines …”
Section: Introductionmentioning
confidence: 99%
“…The use of organoboron compounds as catalysts is attractive because of their ability to predict accurate regioselectivity . In 2011, Taylor reported the first organoboron-catalyzed regioselective modification and glycosylation of carbohydrates using diarylborinic acid as the catalyst. , Based on this pioneering research, regioselective molecular transformations with organoboron compounds, including cyclic borinic acids, boronic acids, and benzoborols, as catalyst have been reported. , Recent advances in this field involves hybrid catalysis, combining organoboron and transition metal complex for regioselective functionalizations of carbohydrates. , Notably, Niu demonstrated a site-divergent terminal propargylation of carbohydrates using a borinic acid/copper hybrid catalytic system . Exploring a similar concept, they discovered site-switchable mono- O -allylation of polyols with Lewis acid/palladium cocatalyst system. Loh et al reported synergistic chiral organoboron/rhodium­(I)-catalyzed regioselective functionalization of carbohydrates …”
mentioning
confidence: 99%